Market-oriented innovation in Hungarian clusters: leveraging strategic capabilities - Stefan Kovács (Innovation & Management Review, 2025)
This study aims to empirically examine how Hungarian-accredited innovation clusters leverage strategic and innovation capabilities to promote market-oriented innovation through enhanced intra-cluster cooperation, particularly under conditions of declining and inconsistent state support. It examines how strategic capabilities, rather than external support, enable clusters to maintain competitiveness and orientation.A mixed-methods approach is used, combining qualitative and quantitative analyses. The qualitative phase involved interviews with key cluster stakeholders, which helped develop the hypotheses and scale items. The quantitative phase surveyed 120 member companies across diverse industries, including information and communications technology, healthcare and machinery. Factor analysis and correlation analysis were employed to assess the relationships between strategic capabilities, intra-cluster cooperation and market orientation, ensuring methodological rigor.The results show that strategic and innovation capabilities significantly improve intra-cluster cooperation, which positively impacts market orientation. Effective coordination and information flow among cluster members are essential for market-driven innovation outcomes. However, a weaker focus on competitor orientation emerged, highlighting an area for improvement in clusters' strategic focus. The research demonstrates how clusters can sustain innovation through internal collaboration and capabilities, even with fluctuating external support.This study adds to the theoretical discourse on market-oriented innovation by providing empirical evidence from Hungarian clusters, a context underexplored in prior research. It extends existing market orientation frameworks by showing the importance of intra-cluster cooperation and internal capabilities for maintaining market relevance, especially in emerging markets. The findings offer practical insights for cluster managers and policymakers on fostering innovation when state support is inconsistent.
Keywords: 650; Innovation clusters; Strategic and innovation capabilities; Market orientation; Innovation; Cooperation